Heritage at the interface : interpretation and identity - Hooper, Glenn; Hooper, Glenn (Cultural heritage studies, 2018)
This volume shows how the term heritage has been used or understood by different groups of people over time. For some, the term has meant a celebration of a particular culture and history or the promotion of accessibility, tolerance, and inclusivity. But for others it has been connected with cultural privilege, social exclusion, or exploitation via the tourism industry. These case studies are taken from America, Britain, Ireland, France, Germany, Austria, India, China, and the Caribbean. The varied approaches to heritage seen here range from the Nazi regime's vision of German national history to the present-day push to recover Native American culture from outdated Hollywood portrayals. Featuring a tribute to Sir Gregory Ashworth, whose influential work drew attention to the contested meanings of heritage, this volume illuminates a fascinating international debate